SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PRODUKTIVITAS TANAMAN TERBAIK DENGAN MENGGUNAKAN METODE TOPSIS - Nina Sari Rizki; Angga Putra Juledi; Deci Irmayani (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
This research aims to solve the problem of selecting plants that have the best agricultural productivity, especially in the Bagan Sinembah area. The selection of these plants is based on plants that are quick to harvest and easy to cultivate, which is done to support food security and the local economy. To overcome the complexity in decision making related to plant selection, this research designed a Decision Support System (DSS) using the TOPSIS Method. This method was chosen because it can provide plant recommendations that are effective, efficient, and in accordance with the specified criteria. The research method involves preliminary studies, determining relevant criteria, and collecting data through field surveys. The criteria used in this research consist of Growth Time, Ease of Cultivation, High Production Yield, Production Cost, and Adaptation to the Environment. Criteria weights are determined based on preference and relative importance. The data is then processed using the TOPSIS method to rank alternative plant choices. The analysis results show the ranking of plants based on their relative proximity scores to positive and negative ideal solutions. The results of this research showed that the recommendation for the plant with the best productivity was Alternative A5 with a preference value of 0.74732. The existence of this decision support system can make a positive contribution to the development of the agricultural sector, especially in increasing the productivity of crops that are quick to harvest and easy to cultivate in the Bagan Sinembah area.